2021
DOI: 10.23887/jlls.v4i2.34443
|View full text |Cite
|
Sign up to set email alerts
|

Validitas Media Pembelajaran E-Learning Berbasis Edmodo pada Materi Sel untuk Peserta Didik Kelas XI SMA/MA

Abstract: Kurangnya kemampuan guru dalam mengembangkan media pembelajaran berbasis teknologi. Selain itu, pada masa pandemi guru mengalami kesulitan dalam menjelaskan materi pembelajaran, karena materi yang banyak dengan waktu yang terbatas. Penelitian ini bertujuan untuk menghasilkan menghasilkan media pembelajaran e-learning berbasis edmodo yang sudah teruji validitasnya pada materi sel kelas XI SMA. Penelitian ini adalah penelitian pengembangan yang menggunakan model pengembangan 4D (Define, Design, Develop, dan Diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The Edmodo application was chosen because it is more effective and interactive (Amalia & Brata, 2018;Cahyawati & Gunarto, 2020;Fatimah & Santiana, 2017). This is in line with the research showed in their research that Edmodo is an effective application to use because there is interaction between teachers, friends, and can be done asynchronously and synchronously (Farman & Chairuddin, 2020;Haruna et al, 2021;Hatip et al, 2019;Miraza et al, 2018;Putri et al, 2021;Sudewa et al, 2021).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The Edmodo application was chosen because it is more effective and interactive (Amalia & Brata, 2018;Cahyawati & Gunarto, 2020;Fatimah & Santiana, 2017). This is in line with the research showed in their research that Edmodo is an effective application to use because there is interaction between teachers, friends, and can be done asynchronously and synchronously (Farman & Chairuddin, 2020;Haruna et al, 2021;Hatip et al, 2019;Miraza et al, 2018;Putri et al, 2021;Sudewa et al, 2021).…”
Section: Introductionmentioning
confidence: 67%
“…Edmodo was an alternative technology used by researchers to overcome problems that arise during the implementation of a pandemic (Anjelina & Mawardi, 2021;Handayani et al, 2021;Putri et al, 2021). The research findings showed that Edmodo can be accessed free of charge so that it was easy to apply to every educational unit.…”
Section: Discussionmentioning
confidence: 95%